IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEDISIPLINAN SISWA MTs (Studi Kasus di MTs Muhammadiyah Campaka) The Implementation of Character Education Management in Improving Student Discipline (A Case Study at MTs Muhammadiyah Campaka) - Nurul Wangsa Maesyaroh; Titi Marlina; Desy Handayani Murni Lira; Bambang Riksa Gelar Perdana; R Supyan Sauri (STKIP Subang, 2026)
Discipline is one of the essential character values that students must possess to support their personal and social development. However, various studies indicate that student discipline remains a challenge in Indonesian education. This study aims to analyze the implementation of character education management in improving student discipline at MTs Muhammadiyah Campaka. The research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving the principal, teachers, homeroom teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that character education management is implemented through planning, organizing, implementation, and evaluation processes. Character education programs are carried out through disciplinary habituation, integration of character values into learning activities, teacher role modeling, and enforcement of school regulations. Evaluation is conducted continuously through monitoring attendance, compliance with school rules, responsibility in learning, and behavioral changes among students. The challenges include family environmental influences, social media exposure, limited supporting facilities, and students' lack of awareness regarding discipline. Solutions include strengthening school-parent collaboration, improving teacher competence, optimizing supporting facilities, and enhancing monitoring and evaluation systems. This study concludes that systematic implementation of character education management effectively improves student discipline at MTs Muhammadiyah Campaka